Significant Relationship Between Brixia Score And The Degree Of Acute Respiratory Distress Syndrome In Covid 19 Patients - Irni Dwi Aprianty Ibrahim; Bambang Satoto; Thomas Handoyono; Antonius Gunawan Santoso; Hermina Sukmaningtyas; FARAH HENDARA NINGRUM (Medica Hospitalia : Journal of Clinical Medicine, 2024)
BACKGROUND: Chest X-ray has an important role in detecting early features of COVID-19. To improve risk stratification, a scoring system in chest x-ray called Brixia Score was developed. The Brixia score is designed to measure the severity of lung abnormalities in COVID-19, with an 18-point severity scale. Deaths in COVID-19 occur mainly due to Acute Respiratory Distress Syndrome (ARDS). ARDS is classified into mild, moderate, and severe degrees. If the degree can be predicted earlier, patients can receive earlier therapy and death rate can be reduced. AIMS:  to analyze relationship between Brixia Score and degree of ARDS in COVID-19 patients. METHOD: the research used an observational analytic method with a cross-sectional approach to 95 subjects who are positive for COVID-19 and diagnosed with ARDS, in January to December 2021. Brixia Score data was collected based on chest X-ray expertise, ARDS degree was based on medical records and blood gas analysis. Analysis of relationship between Brixia score and degree of ARDS was carried out using the Kruskal-Wallis test. RESULT:  There was a significant difference in Brixia score based on degree of ARDS (p value <0.05). The highest Brixia score was obtained in severe ARDS, while the low Brixia score was obtained in mild ARDS. This proves that there is a relationship between Brixia score and degree of ARDS. CONCLUSION: Brixia score has a significant relationship to the degree of ARDS in COVID-19 patients.